Ultrasound Evaluation of Transient Ischemic Attack Caused by Styloid Process Elongation: A Case Report - Li, Zhaoqiang; Hua, Yang; Yang, Jie; Li, Jingzhi (Frontiers in Neurology, 2019)
Stylocarotid artery syndrome (SAS) is a type of Eagle syndrome, which is caused by the compression of the internal or external carotid artery (along with their perivascular sympathetic fibers) by an elongated styloid process, resulting in neurological symptoms including transient ischemic attack (TIA) and cervicofacial pain along the distribution of the artery. The authors describe the case of a 56-year-old man with a history of TIA of unknown origin, who underwent color Doppler flow imaging (CDFI) that detected an elongated styloid process and transcranial Doppler (TCD) monitoring that revealed changes in intracranial blood flow when turning his head. To the best of our knowledge, this report is the first to describe the combination of CDFI and TCD to assess changes in extracranial and intracranial blood flow in patients with suspected SAS.